Implementasi Model Pembelajaran Project Based Learning dan Gaya Belajar Terhadap Keterampilan Proses Sains - Telaumbanua, Indah Lestari; Zega , Rizkiwan Mei Putri Kristiani; Dawolo , Indah Lisa Citrani; Hulu , Besti Ratna; Gulo , Siti Nur Hidayat; Zendrato , Mutiara; Lase, Silvia; Telaumbanua, Fransiska; Harefa, Edward (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the implementation of a project-based learning model with a learning style caused by science process skills. This study used a pseudo-experimental design, two groups participated in this study. The first group is a control group that applies the Direct Instruction learning model with an audio learning style, and an experimental group that applies a Project Based Learning (PBL) learning approach with a kinesthetic learning style. In this study, test sheets were used to assess the extent to which students' science process skills were associated with the content taught in a project-based learning approach environment. The sampling technique used is a non-probability sampling technique (saturated sample) and testing is used as a data analysis technique. Test sheets are used to assess the extent to which a student's science process skills are associated with the content taught in a project-based learning approach environment. The results of the study showed that there was an influence of the direc instruction model with audio learning style, on science process skills and the influence of the PBL model with kinesthetics on the learning style of students